Ageing related down-regulation of myocardial connexin-43 and up-regulation of MMP-2 may predict propensity to atrial fibrillation in experimental animals - Nagibin, V; Egan Benova, T; Viczenczova, C; Szeiffova Bacova, B; Dovinova, I; Barancik, M; Tribulova, N (Physiological research, 2016)
Mechanisms underlying atrial fibrillation (AF), the most common cardiac arrhythmia, particularly in aged population, are not fully elucidated. We have previously shown an increased propensity of old guinea pigs (GPs) heart to inducible AF when comparing to young animals. This study aimed to verify our hypothesis that susceptibility of aged heart to AF may be attributed to abnormalities in myocardial connexin-43 (Cx43) and extracellular matrix that affect cardiac electrical properties. Experiments were conducted on male and female 4-week-old and 24-week-old GPs. Atrial tissue was processed for analysis of Cx43 topology using immunohistochemistry, expression of Cx43 protein using immunobloting, and expression of mRNA of Cx43 and extracellular matrix metalloproteinase-2 (MMP-2) using real time PCR. Immunohistochemistry revealed uniform Cx43 distribution predominantly on lateral sides of the cardiomyocytes of young male and female GP atria. In contrast, non-uniform distribution, mislocalization and reduced immunolabeling of Cx43 were detected in atria of old GPs. In parallel, the atrial tissue levels of Cx43 mRNA were significantly decreased, while mRNA expression of MMP-2 was significantly increased in old versus young GPs. The changes were more pronounced in old GPs males comparing to females. Findings indicate that age-related down-regulation of atrial Cx43 and up-regulation of MMP-2 as well as disordered Cx43 distribution can facilitate development of AF in old guinea pig hearts.
Keywords: myokard; down regulace; Atrial Fibrillation; zvířata; stárnutí; fibrilace síní; Animals; Myocardium; Up-Regulation; Female; matrixová metaloproteinasa 2; morčata; upregulace; Male; ženské pohlaví; mužské pohlaví; Aging; Down-Regulation; Guinea Pigs; Matrix Metalloproteinase 2; konexin 43; Connexin 43